Identification of the Modifier of Min 2 (Mom2) Locus, a New Mutation That Influences Apc-Induced Intestinal Neoplasia - Silverman, Karen A.; Koratkar, Revati; Siracusa, Linda D.; Buchberg, Arthur M.

(untitled) (Genome Research, 2002)
Min (Multiple intestinalneoplasia) mice carry a dominant mutation in the adenomatous polyposis coli (Apc) gene and develop multiple adenomas throughout their intestinal tract (Moser et al. 1990; Su et al. 1992). Polyp multiplicity in Min mice is greatly influenced by genetic background. A modifier locus, Mom1(Modifier of M